Translocation of the endangered apollo butterfly parnassius apollo in southern Finland - Fred M.; Brommer J. (University of Cambridge, 2022)
Translocation of individuals across a barrier which hampers natural colonisation is a potentially important, but debated, conservation tool for a variety of organisms in a world altered by anthropogenic influences. The apollo Parnassius apollo is an endangered butterfly whose distribution retracted dramatically during the 1900s across Europe. In Finland the apollo currently occupies only a fraction of the range of its suitable habitat and is apparently unable to re-colonise other areas. Using eggs collected from wild-caught females from the species’ current Finnish stronghold, a population was reared in order to translocate larvae into an unoccupied, but highly suitable, part of the Finnish archipelago where the species historically occurred until its national decline in the 1950s. In 2009 a restricted number of larvae (1 larva/10 host plants) were released on 25 islands in the inner, middle and outer archipelago zones. In 2010, nine islands situated in all three archipelago zones were (re)stocked with a high density of larvae (1/host plant). In 2011, apollo larval populations were found only on islands in the outer archipelago zone, which were then restocked. The species remained present here in the following two years (2012, 2013) and was hence able to sustain multi-annual population establishment without restocking. Our findings demonstrate that empty suitable habitat may in reality consist of only a few sites where population establishment is possible. Hence, starting the introduction in many sites, which are putatively suitable based on biotic and abiotic criteria derived from species’ existing populations, but then “zooming in” on a smaller set of promising sites showing evidence of successful establishment was key to the success of this translocation.